Prototype for the application of proportional phytosanitaries to the size of trees in citrus (Agroindustria, Sociedad y Ambiente, 2019)
The prevailing need to reduce the use of phytosanitary products, which helps mitigate its effect on the environment, makes it necessary to apply phytosanitary products more precisely, so in this work the design and the first results are presented of the evaluation of an experimental air-assisted sprayer designed to adapt application doses to tree canopy size. The prototype features vertical booms and customized air vents in conjunction with three ultrasonic rangefinders to estimate distances to targeted trees at three different heights. These ranges are continuously being sent to the decision making processor which applies a logic rule based on different criteria adjusted to the specific objectives selected for each application. Multiple field tests were performed in orange groves with varieties Clemenules and Orogrande. After applying a reference volume of 3000 l/ha, results showed that spraying savings up to 30 % are possible while maintaining the same coverage rates.
Keywords: Aplication proportional; citrus; pulverization; sensor